An Econometric Analysis of the Impact of Investment Expenditure on Inflation in Iraq: Evidence from ARDL and Cointegration Approach (2004-2024) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
Investment spending, as a key component of fiscal policy, plays a vital role in influencing economic activities and supporting development processes. This study aims to examine the role of investment spending in reducing economic imbalances, particularly inflation, in the Iraqi economy. The research adopts an analytical approach using economic data to evaluate the relationship between investment spending and inflation rates. The results reveal a significant inverse relationship, indicating that investment spending contributes effectively to reducing inflationary pressures. These findings support the research hypothesis and are consistent with economic theory, which considers investment spending an explanatory variable influencing inflation as a dependent variable. The study recommends enhancing the investment environment by ensuring economic and social stability, which facilitates the implementation of investment projects and contributes to controlling inflation.